Overview of industrial process automation - Sharma, K. L. S. (Elsevier insights., 2011)
Man-made or industrial processes, localised or geographically distributed, need be automated in order to ensure they produce quality, consistent, and cost-effective goods or services. Automation systems for these processes broadly consist of instrumentation, control, human interface, and communication subsystems. This book introduces the basics of philosophy, technology, terminology, and practices of modern automation systems with simple illustrations and examples. Provides an introduction to automation Explains the concepts through simple illustrations and examples Describes how to understand technical documents.